(3JgGaJ GdadGSaIs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s ((3aGNQI HNGQG s)
(3ChdgG (B:s
(3CeG HYO aEfi QCjJ WGFaI jYJbOhf ai GfaSge GdJeff Yf GdGJQGH hGdfWQGA HeRjO GdaWfI hGdPcGA bO QaVRG hXGFa GdGSdGe ef GdYHGOGJ s
(3BNQgG (B:s
(3hCeG fMf adSfG fDKQ GdGf GdNhV ai JcajQ Cgd GdHOY heG jUM efg heG dGjUM cjdG jNQL GdcdGe Yf ebUhO gPG GdcJGH hGddg Gdehab ddUhGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B509s
Keywords: (3GdadSaI hGdefWbs